Estudio de factibilidad para la creación de un “centro de masajes terapéuticos” para la ciudad de Machala, provincia de El Oro - Vivanco Aguilar, Ariana Patricia (2015)
The present research was to determine the feasibility overall objective for creating a "Center of Massage Therapy" for the city of Machala in the province of Gold, was used for the compilation of information the survey technique applied customers (PEA) of the city of Machala, as well as those offering such services, which information concerning the demand was gathered to at a later stage proceed to continue with the feasibility study required to engage in the business, which reaches an acceptable feasibility, so she can be put into practice. The study applied it to a sample of 395 surveys of the economically active population (EAP), information that allowed us to determine the actual demand, effective demand, the share of the company and product offering, obtaining percapita consumption per customer services 48 annually. To make this work the following methods and techniques such as the deductive method, inductive method, descriptive method, analytical method, scientific method and techniques in this paper the literature Technique and Technology of the survey served, were used for steal confidential data, useful and necessary information in this research process and market research technique was applied to the survey it was directed at randomly selected people to obtain valid information that allowed analyze, interpret and detail data more representative in this study process n A total of 399 surveys. Likewise is the administrative organization established with the different hierarchical levels and functions should play each of the persons who will serve on the company. It also has determined its structure and it is anticipated that the life of the project is for a period of five years. The company will have an installed capacity that could provide up to 18,780 services per year; likewise have a capacity used for the first year and 75% each year will increase up to cover 95% of installed capacity. The investment required is of total project investments totaling a value of $ 22,144.08. To finance the project will make use of internal and external sources. Part of the project will be financed from own resources, the with input from partners with 54.84% of investments corresponding to $ 12,144.08 with own funds to cover the total in the project, it is necessary to request a credit, so it is advisable to work with the National Development Bank which provides many facilities to business and opening new businesses; the amount of credit requested is $ 10,000.00 which corresponds to 45.16%, for a term of three years with monthly repayments and annual interest rate of 12%. This loan will finance the adaptations and equipment investment. According to the results of the financial evaluation the project is feasible to implement, demonstrating the positive values of the various indicators such as: Net Worth is achieved in the project is $ 47,869.72 which indicates a positive value; therefore, the decision to invest is convenient, the internal rate of return is 81.1%. The benefit cost is $ 1.40; this means that the indicator if it supports the project, because for every dollar invested 0.40 cents utility will receive. The capital recovery period, will be 1 year, 9 months and 21 days; sensitivity analysis, in case of increase in costs is of 24.90%, and in case of declining revenues is 17.88%, indicating that the project is not sensitive to future changes. Finally, the necessary information used to conduct market research (survey and interview) is attached